Development and forensic efficiency evaluations of a novel multiplex amplification panel of 17 Multi-InDel loci on the X chromosome - Jin, Xiaoye; Ren, Zheng; Zhang, Hongling; Wang, Qiyan; Liu, Yubo; Ji, Jingyan; Yang, Meiqing; Zhang, Han; Hu, Wen; Wang, Ning; Wang, Yicong; Huang, Jiang (Frontiers in Ecology and Evolution, 2022)
Multi-InDel, as the novel genetic markers, showed great potential in forensic research. Whereas, most scholars mainly focused on autosomal Multi-InDels, which might provide limited genetic information in some complex kinship cases. In this study, we selected 17 Multi-InDels on the X chromosome and developed a multiplex amplification panel based on the next generation sequencing (NGS) technology. Genetic distributions of these 17 loci in Beijing Han, Chinese Southern Han, and the studied Guizhou Han populations revealed that most loci showed relatively high forensic application values in these Han populations. In addition, more allelic variations of some loci were observed in the Guizhou Han than those in Beijing Han and Southern Han populations. Pairwise FST values, multi-dimensional analysis and phylogenetic tree of different continental populations showed that selected 17 loci generally could differentiate African, European, East Asian, and South Asian populations. To sum up, the developed panel in this study is not only viewed as the high-efficient supplementary tool for forensic individual identification and paternity analysis, but it is also beneficial to inferring biogeographical origins of different continental populations.